Al-Chemy: e-Learning Platform for Foundation Students - Nur Ilyana Ismarau Tajuddin; Nurul Jannah Abd Rahman; Khairi Azhar Aziz; Noorrezam Yusop; Nor Aziyatul Izni (Institute of Advanced Engineering and Science (IAES) in collaboration with Intelektual Pustaka Media Utama (IPMU), 2024)
Indexed by Scopus